Hestia to Demeter: Reducing Agrochemical Pollution to Empower Women Farmers - Fardoun, Aya; Elhusseini, Rami I; Jawdah, Youssef Abou (Journal of Sustainability Perspectives, 2024)
The 2020 Farm to Fork strategy by the European Commission aimed to reduce agrochemical pollutants and protect biodiversity but stirred controversy due to conflicts between intensive agriculture demands and environmental priorities. Strict limits on agrochemical residues required farmers to produce less. The de-intensification and agroecology prone policy impacted livelihoods, sparking political upheaval. Due to lack of pesticide alternatives and extension services, Lebanese exports have faced challenges complying with residue restrictions. Agricultural laborers and consumers are exposed to high levels of pesticide residue. Undocumented refugee women form a significant part of the agricultural workforce, and women led agricultural cooperatives have minimal access to funding, exacerbating gender inequity. The American University of Beirut (AUB) has played a pivotal role in agroecology research, rural development, and gender equity. Knowledge transfer promotes civic awareness and private sector partnerships. Local Natural enemies and parasites emerged as a residue-free alternative to agrochemicals. Biocontrol-based integrated pest management holds great potential for mitigating pesticides hazards to human and environmental health. Launching the “natural predators” initiative from women-run farms holds a great promise in dually resolving the problems of agrochemical pollution and gender equity in the agricultural sector. Empowering women in agriculture aims to transform their role from care work to farm management. This paper focuses on the technical aspects of developing “natural enemies” as pesticides alternative for Lebanese agriculture, aiming to overcome export challenges and revitalize the economy. "Farm to Fork meets Hestia to Demeter" underscores AUB's commitment to sustainability aligns climate action with gender equity. By supporting women entrepreneurs and addressing climate change's impact on public health, the initiative contributes to AUB's broader mission of advancing Lebanon and the region through Education for Sustainable Development.